Morphological and morphometric aspects of early life stages of piabanha Brycon gouldingi (Characidae) - Faustino, F. [UNESP]; Makino, L. C. [UNESP]; Neumann, E.; Nakaghi, L. S. O. [UNESP] (Wiley-Blackwell, 2015)
Adult specimens of piabanha Brycon gouldingi were collected from Rio das Mortes (Mato Grosso, Brazil), adapted to captivity and induced to spawn at Buriti Fisheries (Nova Mutum, MT, Brazil). The early developmental stages of B. gouldingi were then characterized. Samples were collected at pre-determined times from oocyte extrusion to total yolk absorption. Oocyte diameter, total larval length (L-T) and yolk-sac volume were measured. The mean +/- s.d. duration of embryo developmental of B. gouldingi was 1390 +/- 006 h at 2640 +/- 113 degrees C. The mean +/- s.d. oocyte diameter was 113 +/- 006 mm with 54% of oocytes ranging from 111 to 120 mm. Seven stages characterized the early developmental phase of this species: zygote, cleavage, morula, blastula, gastrula, histogenesis-organogenesis and hatching, with unique features related to each stage. At hatching, the larvae measured 340 +/- 007 mm, presented an elongated shape with yolk-sac volume of 046 +/- 008 mu l, non-pigmented eyes and exhibited swimming ability. When the yolk was completely absorbed at 55 h post-hatch, mean +/- larval L-T was 668 +/- 065 mm, the eyes were highly pigmented and the teeth were visible. These are the first reported findings on the initial developmental stages of B. gouldingi and could be used to improve captive breeding management and conservation practices.
Keywords: early development; embryos; histogenesis; larvae; organogenesis; ontogeny